PERAN GRIT DALAM MEMPREDIKSI STRES AKADEMIK MAHASISWA PADA TAHAP PENYUSUNAN SKRIPSI - Fabrianne , Michelle; Ferdian, Flaviana Rinta (MANASA, 2025)
This study aims to examine the role of grit on academic stress among final-year students in Indonesia. In this study, the researcher employed a quantitative method with regression analysis. The measurement tools used were the Skala Stres Akademik and Skala Grit. The sample consisted of 297 students currently working on their theses, selected through non-probability sampling techniques. The findings show that grit significantly predicts academic stress. This indicates that grit helps students develop a more positive perception of academic stressors and serves as a psychological resource that enables them to remain diligent and resilient in facing the challenges of thesis writing. For future research, it is recommended to explore the strongest predictors or correlations between factors influencing grit and levels of grit.